27: Machine learning and law - Porębski, Andrzej (Edward Elgar Publishing, 2023)
This chapter will provide an overview of the applications of machine learning in the legal domain, both theoretical possibilities and applications already in use. As an understanding of IT concepts is crucial for a comprehensive discussion of their applications, the chapter opens with an informal introduction to machine learning. In the following sections, the most relevant applications (primarily COMPAS system) and the discourses surrounding them are presented. The predictive justice trend is then considered and some applications of machine learning in legal practice are briefly pointed out. To recognise the tensions created by the prospect of the proliferation of machine learning in the application of law, especially in the judiciary, an understanding of the problems of transparency is significant. Thus, the last part of the text is devoted to the eXplainable Artificial Intelligence trend and an overview of the considerations of transparency and intelligibility of machine learning applied in law.